Chemical input reduction in the arabinoxylan and lignocellulose alkaline extraction and xylooligosaccharides production. (March 2017) - de Figueiredo, Franciane Cristina; Carvalho, Ana Flavia Azevedo; Brienzo, Michel; Campioni, Tania Sila; de Oliva-Neto, Pedro
Highlights: Improvement of alkaline method for obtaining arabinoxylan and lignocellulose. Higher temperature, lesser chemicals and shorter time in the efficient extraction. Arabinoxylan and lignocellulose extracted in high level from sugarcane bagasse. Efficient arabinoxylan hydrolysis for XOS or xylose obtaining by xylanases. XOS or xylose produced from arabinoxylan depend on fungal xylanase. Abstract: Lignocellulosic material breakdown by hydrolysis is an important step to open new perspectives for bioenergy and special foods production like prebiotic xylooligosaccharides. Improvement of lignocellulose and arabinoxylan alkaline extraction from sugarcane bagasse and enzymatic hydrolysis were performed. Treatments 1 (10% KOH at 70 °C), 3 (5% KOH at 121 °C) and ZD method (24% KOH at 35 °C) showed solid lignocellulose recovery of respectively 75.2%, 74.2% and 73%. A range of 24.8–27% extracted material with high arabinoxylan content (72.1–76.3%) was obtained with these treatments. Treatment 1 and 3 exhibited great KOH reduction in the method reaction, 54.1% and 76.2%, respectively. Likewise, in treatment 3 there was a decrease in ethanol consumption (40.9%) when compared to ZD method. The extracted arabinoxylan showed susceptibility to enzymatic hydrolysis with high solid loading (7%) since Trichoderma reesei xylanases were advantageous for xylose production (54.9%), while Aspergillus fumigatus xylanases achieved better XOS production (27.1%).